Evidence for the presence of chondrule‐ and CAI‐derived material in an isotopically anomalous Antarctic micrometeorite. (24th November 2020) - Soens, Bastien; Suttle, Martin D.; Maeda, Ryoga; Vanhaecke, Frank; Yamaguchi, Akira; Van Ginneken, Matthias; Debaille, Vinciane; Claeys, Philippe; Goderis, Steven
Abstract: We report the discovery of a unique, refractory phase‐bearing micrometeorite (WF1202A‐001) from the Sør Rondane Mountains, East Antarctica. A silicate‐rich cosmic spherule (~400 µm) displays a microporphyritic texture containing Ca‐Al‐rich inclusion (CAI)‐derived material (~5–10 area%), including high‐Mg forsterite (Fo98‐99 ) and enstatite (En98‐99, Wo0‐1 ). The micrometeorite also hosts a spherical inclusion (~209 µm), reminiscent of chondrules, displaying a barred olivine texture. Oxygen isotopic compositions of the micrometeorite groundmass (δ 17 O = –3.46‰, δ 18 O = 10.43‰, ∆ 17 O = –1.96‰) are consistent with a carbonaceous chondrite precursor body. Yet, a relict forsterite grain is characterized by δ 17 O = –45.8‰, δ 18 O = –43.7‰, ∆ 17 O = –23.1‰, compatible with CAIs. In contrast, a relict low‐Ca pyroxene grain (δ 17 O = –4.96‰, δ 18 O = –4.32‰, ∆ 17 O = –2.71‰) presumably represents a first‐generation silicate grain that accreted 18 O‐rich gas or dust in a transient melting scenario. The spherical inclusion displays anomalous oxygen isotope ratios (δ 17 O = –0.98‰, δ 18 O = –2.16‰, ∆ 17 O = 0.15‰), comparable to anhydrous interplanetary dust particles (IDPs) and fragments from Comet 81P/Wild2. Based on its major element geochemistry, the chondrule size, and oxygen isotope systematics, micrometeorite WF1202A‐001 likely sampled a carbonaceous chondrite parent body similar to, but distinct from CM, CO, or CV chondrites. This observation may suggest that some carbonaceous chondrite bodies can be linked to comets. The reconstructed atmospheric entry parameters of micrometeorite WF1202A‐001 suggest that the precursor particle originated from a low‐inclination, low‐eccentricity source region, most likely either the main belt asteroids or Jupiter family comets (JFCs).